PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN MUSI RAWAS - Wisdalia Maya Sari; Fitria Fitria; Erik Astrada (LPPM UNIVERSITAS BINA INSAN, 2019)
This study aims to find out 1) The influence of Organizational Culture on Employee Performance in the Industry and Trade Service of Musi Rawas Regency, 2) The Effect of Work Motivation on Employee Performance in the Industry and Trade Service of Musi Rawas Regency, 3) The Effect of Organizational Culture and Work Motivation simultaneously on the Performance of Employees at the Department of Industry and Trade Musi Rawas Regency. Hypothesis Testing partially independent variables (Organizational Culture) on the dependent variable Employee performance at the Department of Industry and Trade Musi Rawas Regency that is equal to 3,173 ≥ table 1,674. While partially independent Hypothesis Test (Work Motivation) on the dependent variable employee performance at the Department of Industry and Trade Musi Rawas Regency that is equal to 3,042 ≥ (1,674) At a significant level of 5%, then partially the independent variable has a significant effect on the dependent variable . Variations in changes to the dependent variable (Employee Performance) can be explained by the independent variables (Organizational Culture and Work Motivation) simultaneously (57.0%) and the remaining 43.0% is influenced by other variables. Regency Testing Hypothesis Testing with the F test obtained a Fcount value of 32.477 ≥ 3.18. and the significance level simultaneously sig F is 0,000 α α (0.05), at a significant level of 5%, the Organizational Culture and Work Motivation together on the Performance of employees at the Department of Industry and Trade Musi Rawas Regency.